Statistical Cost Analysis Re-Revisited: Comment - Maddala, G. S.; Roberts, R. Blaine (Quarterly Journal of Economics, 1981)
G. S. Maddala, R. Blaine Roberts; Statistical Cost Analysis Re-Revisited, The Quarterly Journal of Economics, Volume 96, Issue 1, 1 February 1981, Pages 177–181